Effect of warm-up on muscle oxygenation and metabolism in supramaximal cycling - Wittekind, A.; Cooper, C. E.; Elwell, C. E.; Leung, T. S.; Angus, C.; Beneke, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The effect of a warm-up induced increase in blood lactate prior to performance is unclear and may be unwarranted in severe exercise where a reduced glycolytic rate may compromise performance. PURPOSE To examine the effect of warm-ups which raised blood lactate concentration (BLC) to different levels on muscle oxygenation and metabolism in a supramaximal cycling sprint test. METHODS 8 trained male cyclists undertook a 30s sprint test from stationery seated start (load 0.09 x body mass (kg)) preceded by one of 3 warm-up protocols: WE 6 min at 40% peak aerobic power (PAP); WM 5 min at 40% PAP + 1 min at 80% PAP; WH 5 min at 40% PAP + 1 min at 110% PAP - each followed by 10 min seated recovery. Pulmonary oxygen uptake (VO2p), and muscle oxygenation as measured by near infrared spectroscopy (oxyhemoglobin (O2Hb), deoxyhemoglobin (HHb), total hemoglobin (Hbtot) and tissue oxygenation index (TOI)), were measured throughout. The responses of HHb and TOI during the sprint were analysed using a monoexponential model with time delay. The off kinetics of VO2p were analysed using a biexponential model. Blood lactate kinetics of the sprint were analysed with a biexponential model predicting extravascal lactate generation. RESULTS Mean power during the sprint was reduced in WH compared to WE (WE 672±54 WM 666±56 WH 655±59 W p<0.05) and was primarily due to lower mean power during the first 5s. BLC was different prior to the start of each sprint (WE 0.9±0.4 WM 1.9±0.6 WH 4.4±0.9 mmol.L-1 p<0.05) and extravascal lactate generation during the sprint was reduced by each increment in warm-up (WE 12.4±1.7 WM 11.0±1.5 WH 9.5±1.8 mmol.L-1 p<0.05). VO2p was higher than rest prior to each sprint but not different between conditions and with no difference in mean VO2p during the sprint (WE 1.5±0.2 WM 1.5±0.2 WH 1.5±0.3 L p>0.05). There was no difference in the area under the fast component of VO2p off kinetics though this tended to be higher for WH compared to WM and WE (WE 2.2±0.4 WM 2.3±0.4 WH 2.6±0.6 L). NIRS data indicated that oxygen delivery was increased prior to sprints but not different between conditions. There was no difference between warm-ups for the on kinetics of HHb or TOI. However there was a tendency for the TOI time delay for WH to be shorter (WE 3.7±1.6 WM 4.0±0.5 WH 2.9±1.2 s p<0.06). CONCLUSION An apparent increased PCr hydrolysis as indicated by the higher area under the fast component of VO2p off kinetics could not fully compensate for the reduced glycolytic rate in the sprint following WH which was itself indicated by a reduced extravascal lactate generation. All warm-ups increased muscle oxygenation to the same extent prior to the sprint and there was no difference in oxygen delivery/utilisation or VO2p during the sprint despite WH tending to increase apparent PCr hydrolysis. It appears that warm-up may reduce glycolytic rate and for harder warmups other energy sources may not be able to fully compensate in severe intensity exercise.